Vertically Stacked Soliton‐Like Domain Walls in Nematic Liquid Crystals. Issue 11 (4th October 2021) - Jones, Reed; Melnyk, Olha; Macêdo, Rair; Camley, Robert E.
Abstract: In the standard liquid crystal (LC) geometry, one generally finds a quasi‐parabolic director profile in the vertical direction, where the directors are aligned with an applied field in the center of the cell. In contrast, using a numerical energy minimization approach, we find that there are multiple metastable solutions where the director profile is oscillatory. At low voltages, we find small oscillations, which evolve into standard soliton‐like domain walls as the applied voltage is increased. We predict the thickness of the domain wall with a simple analytic model that gives a good comparison to our numerical calculations, in the standard domain wall regime. For dual‐frequency nematic LCs, the occurrence of this regime can be tuned by a change of the biasing frequency. Moreover, we investigate how domain walls can affect the optical properties of LC‐based devices. For instance, we find that the transmittance curve shifts to higher voltages as domain walls are introduced. This shift can be used to create an efficient tunable filter. Abstract : In the standard liquid crystal (LC) geometry, one generally finds that the LC molecules align with the applied field. In contrast, the authors found that there are multiple metastable solutions where the LC molecules' orientation is oscillatory and can converge into periodic soliton‐like solutions. The authors predict the thickness of the soliton‐like domain wall with a simple analytic model.